Lindsaeoid ferns of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2005)
The paper deals with two genera of the family Lindsaeaceae, namely, Lindsaea (with 4 species, L. ensifolia, L. odorata, L. lucida and L. doryphora) and Sphenomeris (with only S. chinensis) from Bangladesh. Key words: Lindsaeoid ferns, Pteridophyte, Bangladesh DOI: 10.3329/bjpt.v12i2.599 Bangladesh J. Plant Taxon. 12(2): 11-18, 2005 (December)